Determination of temperature-dependent otolith oxygen stable isotope fractionation on chum salmon Oncorhynchus keta based on rearing experiment - Gou, Yuxiao; Higuchi, Tomihiko; Iino, Yuki; Nagasaka, Tsuyoshi; Shimizu, Yuichi; Shirai, Kotaro; Kitagawa, Takashi (Frontiers in Marine Science, 2022)
Reconstruction of water temperatures experienced by marine fishes using otolith oxygen stable isotopes (δ18O) as natural thermometers has been proven to be a useful approach for estimating migration routes or movement patterns. This method is based on the mechanism that the equilibrium fractionation of δ18Ootolith against ambient water exhibits a species-specific thermal sensitivity during the process of otolith aragonitic CaCO3 precipitation. In this study, a laboratory-controlled rearing experiment was conducted to determine the temperature dependency of δ18O fractionation on the anadromous fish species, chum salmon (Oncorhynchus keta), of which the detailed migration routes have not been elucidated yet. To test that temperature was the only factor affecting δ18Ootolith fractionation, this study ensured a relatively stable rearing condition, evaluated the isotope composition of the rearing water, and analyzed carbon isotope (δ13Cotolith) to examine the potential effect of kinetic and metabolic isotopic fractionations. The δ18Ootolith fractionation equation on chum salmon was thereby determined within a temperature range of 9–20℃ and was indistinguishable from the equation of synthetic aragonite; The δ13Cotolith was affected by both physiological processes and δ13CDIC; In lower temperatures settings, both oxygen and carbon isotopes depleted simultaneously. This study suggests that the chum salmon species-specific oxygen isotope fractionation equation could be used on reconstruction of temperature history and also throw insights into understanding the incorporation of oxygen and carbon sources during calcification process for otoliths.